BLENDED LEARNING WITH FLIPPED CLASSROOM TYPE FOR ENHANCING QUALITY OF LEARNING IN VOCATIONAL HIGH SCHOOL: A REVIEW - Basori Basori (VANOS Journal of Mechanical Engineering Education, 2018)
Learning in the current disruption era requires a model that can integrate information technology in learning in VHS. This review aims to examine the flipped classroom learning model that is rapidly evolving today. The method was a literature review. The review was conducted on 30 articles in reputable journals. The results show that: (1) The flipped classroom is learning model by face-to-face and online meeting. (2) The flipped classroom is very applicable in vocational education because it accommodates the student activities needed in the vocational world. (3) Flipped classroom procedure: Introduction by providing materials at the online action, then do face-to-face meeting by forming groups, afterward make group assigned tasks, then activate group by discussing works, finally, the group presenting assignments in class. (4) Flipped classroom weakness: the teacher can not control student activity, the readiness of teacher and student, limited the technology